Improved reservoir description using surface oil viscosity data (2003)
Subsurface oil viscosity data are usually not readily available for most reservoirs, as they are expensive to acquire. On the other hand, surface oil viscosity is routinely measured and therefore readily available for all producing wells. A method has been developed for converting the surface viscosity to reservoir viscosity data, using SPDC's "Field A" as a case study. Surface oil viscosity data from all producing wells in "Field A" where collected from SPDC-West Production Chemistry laboratory and converted to reservoir viscosity using a simple method that utilizes relevant PVT data. The method allows a better and more detailed subsurface description of reservoir viscosity in line with facies variations. The study also shows that reservoir oil viscosity could be lower in some sands than previously estimated. This gave a significant impact on reserves in one of the reservoirs where scope to increase the booked reserves by about 60 MMstb was observed. Opportunity to also –increase constrained off take from 2300 b/d to 3000 b/d in some planned new wells was also observed.